MASW for the microzonation of earthquake hazard in Banjar City, West Java, Indonesia. Issue 1 (March 2021) - Muzli, Muzli; Kambali, Retno A P; Rohadi, Supriyanto; Rachman, Asep N; Nugraha, Jimmi; Susilanto, Pupung; Sulastri,; Pakpahan, Suliyanti; Setyonegoro, Wiko; Florida, Nelly R; Karnawati, Dwikorita
Abstract: Efforts to reduce the impact of earthquake disaster have been made by the government, continuously. To decrease the casualties, an effort to be done is to construct housings and public infrastructures following the earthquake-resistant role or building code, especially in cities with high vulnerability and population. For this reason, an earthquake hazard microzonation map is crucial. Microzonation of earthquake hazard in Banjar City, West Java, Indonesia, was conducted by mapping the surface soil classification. Banjar is an essential city in West Java, connecting Bandung and the cities in the southern part. The microzonation mapping was done using the MASW (Multichannel Analysis of Surface Waves) method. The fieldwork of Vs30 measurements has been conducted in February 2020. We recorded 31 MASW sites in the entire Banjar City area with the distance between the locations approximately 5km. The results of this study indicate the surface soil classification in Banjar City in detail and precisely. The eastern part of the city shows a relatively softer surface soil structure compared to the western part. Comparison of the microzonation map obtained from the measurements with empirical Vs30 map (average shear waves velocity down to 30m), geology structure, and topographic data, showing good agreement. The earthquake microzonation map is recommended to be considered one of the references for developing the building code.